Microblade Technology in Quartz during the Mesolithic in Eastern Middle Sweden - Fredrik Molin; Roger Wikell (Current Swedish Archaeology, 2008)
Thc authors present a material that has previously not been given much attcntion : microblades and microblade cores of quartz from eastern middle Sweden. The focus is on the technology. core types, geographical distribution and dating. The debate on how to interpret the quartz material ofthe region in cultural tenns and the role of the microblade technology in this discussion, are also dealt with. During recent years, many excavations and special surveys have supplied the archaeologists in easterll middle Sweden with new source material. An increased knowledge of quartz is an important factor in the dcvclopment of this field of research. The authors found it vely helpful to discuss the newly found cores and blades and their technical execution with Kjel knutsson of Uppsala University. Gcnerally speaking, the Mesolithic quartz materials from eastern middle Sweden are dominated by two methods ol'reduction; freehand-platform and bipolar-on-anvil. The latter method regularly produces thin flakcs that resemble microblades. In this articlc, however, focus will be on microblades sensu stricto. It seems that the production of'quartz microblades is more common than previously thought. Early reports from sites such as Sjövreten and Skumparberget are no longer anomalies.